Character variation of root space microbial community composition in the response of drought-tolerant spring wheat to drought stress - Fang, Jing; Wei, Shuli; Gao, Yanrong; Zhang, Xiangqian; Cheng, Yuchen; Wang, Jianguo; Ma, Jie; Shi, Gongfu; Bai, Lanfang; Xie, Rui; Zhao, Xiaoqing; Ren, Yongfeng; et al. (Frontiers in Microbiology, 2023)
Drought is the most prevalent environmental stress in crop production, posing a significant danger to food security. Microorganisms in the crop root zone affect crop growth and development, enhance effective nutrient use, and resist adversity hazards. To analyze the changes and functional differences of root space microbial (endosphere-rhizosphere-bulk soil) communities in spring wheat under drought stress. In this study, the root, rhizosphere, and bulk soil of the drought-tolerant group (DTG, three varieties) and drought-sensitive group (DSG, three varieties) were collected. The control (CK, 25–28%), moderate drought (MD, 15–18%), and severe drought (SD, 9–12%) were analyzed by high-throughput sequencing and bioinformatics. The results showed significant differences in the diversity of Bacteria and Fungi in the root space of spring wheat under drought stress (P < 0.05), with the drought-tolerant group exhibiting higher microbial diversity. The microbial community change in spring wheat root space was mainly determined by the niche differentiation of endosphere, rhizosphere, and bulk soil and declined from endosphere to bulk soil due to drought. The antagonism between microbial and root-space species increased, and the community’s complexity and stability deteriorated. Enriching drought-resistant preference groups like Actinobaciota, Variovorax, Streptomyces, and Conocybe altered the structure and function of the microbial community in the root space of spring wheat. Spring wheat’s root space Bacteria and Fungi have different strategies to respond to drought.